The causal relationship between government and tax revenue in Barbados - Maynard, Tracy ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Investigates the interrelationships between total government expenditure and total tax revenue in Barbados using a multivariate cointegrating model.